Stocks, memes, and desperation capitalism: an ethnographic case study of r/WallStreetBets - Nani, A (2023)
Increased availability of digital technologies, such as consumer-level investing platforms, have democratised the financial services industry. Similarly, social media has provided a new forum for retail investors, individuals who are investing without institutional support, to find and share financial advice. Against the backdrop of institutional distrust spurred by the 2008 economic crisis and the COVID-19 cost-of-living crisis, retail investors increasingly turn to investment communities on social media, viewing the stock market as an escape from financial uncertainty. Though prior research has demonstrated that investments made based on information provided from social media largely results in losses, online investing communities, most notably r/wallstreetbets, have continued to attract new users. In this thesis, I demonstrate how social media influences the behavior of retail investors and explain why they are drawn to social media investing communities despite the high likelihood of incurring losses. To conduct this research, I undergo an ethnographic case study of r/wallstreetbets, an online investing community hosted on Reddit known for anti-institutional meme culture and high-risk investment advice. The results demonstrate that users prone to economic biases have their vulnerabilities amplified by social media. Anti-institutional sentiment spurred by lingering resentment for institutions and their role in creating economic crises causes users to trust unregulated information on social media over the regulated advice provided by banks. The investment advice on social media incentivizes users to pursue unnecessarily high-risk trades, exemplified by ‘YOLO trading’ commonly seen on r/wallstreetbets. This culminates in a theory of desperation capitalism, describing why young people feel forced to adopt high-risk money-making strategies to escape financial precarity. The findings of this thesis can help policy-makers, institutions, and academics understand what draws retail investors to social media for advice, resulting in better strategies to mitigate the impacts of dubious online investment advice.